2016
DOI: 10.1099/mic.0.000343
|View full text |Cite
|
Sign up to set email alerts
|

DprA is required for natural transformation and affects pilin variation in Neisseria gonorrhoeae

Abstract: Natural transformation is the main means of horizontal genetic exchange in the obligate human pathogen Neisseria gonorrhoeae and drives the spread of antibiotic resistance and virulence determinants. Transformation can be divided into four steps: (1) DNA binding, (2) DNA uptake, (3) DNA processing and (4) DNA recombination into the chromosome. The DNA processing enzyme DprA has been shown to shuttle incoming ssDNA to the recombination enzyme RecA during transformation in Bacillus subtilis and Streptococcus pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…In Bacillus subtilis, DprA also loads RecA onto transforming ssDNA (Yadav et al, 2013), although inactivation of dprA results in a more modest ~50-100-fold loss of transformation efficiency (Yadav et al, 2012). DprA also plays a role in transformation, presumably as a RMP, in Haemophilus influenzae (Karudapuram et al, 1995), Neisseria gonorrhoeae (Duffin and Barber, 2016), Neisseria meningitidis (Hovland et al, 2017) Campylobacter jejuni (Takata et al, 2005), and Helicobacter pylori (Ando et al, 1999;Smeets et al, 2000). Although the mechanism of transformation remains broadly conserved across transformable bacteria, the regulation of competence is very diverse (Johnston et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Bacillus subtilis, DprA also loads RecA onto transforming ssDNA (Yadav et al, 2013), although inactivation of dprA results in a more modest ~50-100-fold loss of transformation efficiency (Yadav et al, 2012). DprA also plays a role in transformation, presumably as a RMP, in Haemophilus influenzae (Karudapuram et al, 1995), Neisseria gonorrhoeae (Duffin and Barber, 2016), Neisseria meningitidis (Hovland et al, 2017) Campylobacter jejuni (Takata et al, 2005), and Helicobacter pylori (Ando et al, 1999;Smeets et al, 2000). Although the mechanism of transformation remains broadly conserved across transformable bacteria, the regulation of competence is very diverse (Johnston et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…DprA in bacteria is so far shown to be required for competence for DNA transformation [4] and suggested to be involved in RecA-mediated pilin variation [19]. The presence of a dprA gene has been suggested to be a distinctive feature of naturally transformable species [27].…”
Section: Discussionmentioning
confidence: 99%
“…Using a transposon mutant screen in Nm, Tang and co-workers showed that the dprA null mutant exhibits total loss of competence for DNA transformation [4]. The Nm and Ng dprA null mutants are non-transformable regardless of the type of donor DNA substrate, and Ng DprA is suggested to be involved in RecA-mediated pilin variation [4, 19]. HGT in Haemophilus influenzae, S. pneumoniae , and B. subtilis is associated with DprA [8, 15, 20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…The driving force for translocation of ssDNA across the IM may be provided by an ATPase (ComFA), which is also widely conserved in bacteria ( Londono-Vallejo and Dubnau, 1994 ; Takeno et al, 2011 ; Chilton et al, 2017 ; Diallo et al, 2017 ). After translocation of ssDNA, DprA, and RecA bind ssDNA and catalyze the formation of joint DNA molecules for homologous recombination ( Mortier-Barriere et al, 2007 ; Dwivedi et al, 2013 ; Yadav et al, 2013 , 2014 ; Duffin and Barber, 2016 ; Diallo et al, 2017 ; Hovland et al, 2017 ; Le et al, 2017 ). In this way, the incoming foreign ssDNA displaces one strand of the chromosomal dsDNA ( Mortier-Barriere et al, 2007 ), followed by being converted to homogeneous dsDNA through DNA replication.…”
Section: Pull Dna In During Natural Transformationmentioning
confidence: 99%